The Evolution of Electric Vehicle Charging Technologies in Nigeria: Prospects and Challenges - Sunday, Philip (International Journal of Education, Management, and Technology, 2024)
This study examines the evolution of electric vehicle charging technologies in Nigeria, focusing on the current state of charging infrastructure, challenges to adoption, effectiveness of government policies, and the role of private sector participation. Utilizing a quantitative research methodology, data were collected from 400 respondents across major urban centers. The findings reveal that Nigeria's electric vehicle charging infrastructure is still in its infancy, with only 180 charging stations, including 30 fast charging points, predominantly located in urban areas. Key challenges identified include inadequate charging infrastructure, unreliable electricity supply, low public awareness, high initial costs, and limited vehicle availability. The analysis of government policies shows mixed effectiveness, with positive feedback on the National Electric Vehicle Policy but lower ratings for initiatives from the Nigerian Electricity Regulatory Commission. Additionally, the study underscores the significant role of private sector investment in expanding charging networks, highlighting the potential for public-private partnerships to drive innovation and infrastructure development. The recommendations aim to enhance the adoption of electric vehicles in Nigeria by prioritizing infrastructure development, increasing public awareness, enhancing policy support, and fostering private sector involvement. This research provides a foundation for future studies and policy considerations to promote electric mobility in Nigeria, contributing to environmental sustainability and economic growth.